The Evolving Screen: An Autoethnographic Journey of English Proficiency and Technological Shifts - Ardhi Eka Fadilah; Siusana Kweldju; Suhono Suhono; Raisha Nur Anggraini; Yeasy Agustina Sari (Bulletin of Pedagogical Research, 2025)
This autoethnographic study explores the author's long-term journey in learning English through the lens of Deeper Learning, emphasizing the transformative role of evolving digital technologies. From early reliance on analog tools such as cassette tapes and printed dictionaries to the adoption of artificial intelligence, chatbots, and mobile applications, the narrative traces how each technological era has reshaped language learning practices. Through thematic analysis of personal experiences, three key insights emerge: the expansion of immersive learning via digital access, enhanced learner autonomy through personalized technologies, and the development of hybrid human-AI interactions in language acquisition. The study reveals that technology serves not merely as a supplementary aid but as an active mediator that cultivates critical thinking, collaboration, and communicative competence. The key contribution of this study lies in providing a reflective, experience-based perspective that bridges personal narrative with theoretical understanding, offering valuable insights for educators, curriculum designers, and language learners on how to meaningfully integrate technology into language education. These insights call for a reimagining of English language classrooms integrating formal instruction with learner-driven, technology-enabled ecosystems.